Analisis Jaringan Pipa Hidran di Summarecon Mall Bandung - Kelvin Dwiputra; Olga Catherina Pattipawaej (Universitas Kristen Maranatha, 2025)
A fire hydrant is a pipe connected to a water channel, especially on a street, which is used to take water from the main channel to extinguish a fire. The hydrant pipe network system is a distribution system used to channel water from sources to fire hydrants to extinguish fires. Installing a hydrant network is an important part of the security and safety of a building, especially in commercial spaces such as shopping centers. The aim of this final assignment research is to understand the distribution system of the hydrant pipe water network at Summarecon Mall Bandung. This final project has a scope, namely the implementation method which is carried out by analyzing through EPANET software. Several SNI regulations regarding hydrants were used in this research.With this research regarding the installation of hydrant pipe networks, it is concluded that the water discharge resulting from EPANET 2.2 results can provide sufficient water supply to extinguish fires. For advice, it is hoped that routine inspections of the pipe network can be maintained in optimal condition. The safety of the Summarecon Mall Bandung shopping center can be further improved by ensuring that the installation of the hydrant pipe network remains effective and efficient. Keywords: Hydrants, Pipe Networks, EPANET 2.2, Summarecon Mall Bandung.